2016
DOI: 10.1155/2016/5435092
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Segment Imaging in Ocular Surface Squamous Neoplasia

Abstract: Recent advances in anterior segment imaging have transformed the way ocular surface squamous neoplasia (OSSN) is diagnosed and monitored. Ultrasound biomicroscopy (UBM) has been reported to be useful primarily in the assessment of intraocular invasion and metastasis. In vivo confocal microscopy (IVCM) shows enlarged and irregular nuclei with hyperreflective cells in OSSN lesions and this has been found to correlate with histopathology findings. Anterior segment optical coherence tomography (AS-OCT) demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…In addition, we found that while AS‐OCT is a reliable tool for the broad clinical diagnosis of OSSN, it was unable to consistently differentiate between invasive and non‐invasive tumours. These findings emphasize that neither AS‐OCT imaging nor clinical appearance alone can be used to reliably identify invasion, which is consistent with the AJCC's current heightened emphasis on biopsy with histopathologic analysis for OSSN staging (particularly for stages Tis, T1 and T2, for which depth of histopathologic invasion is explicitly defined).…”
Section: Discussionsupporting
confidence: 79%
“…In addition, we found that while AS‐OCT is a reliable tool for the broad clinical diagnosis of OSSN, it was unable to consistently differentiate between invasive and non‐invasive tumours. These findings emphasize that neither AS‐OCT imaging nor clinical appearance alone can be used to reliably identify invasion, which is consistent with the AJCC's current heightened emphasis on biopsy with histopathologic analysis for OSSN staging (particularly for stages Tis, T1 and T2, for which depth of histopathologic invasion is explicitly defined).…”
Section: Discussionsupporting
confidence: 79%
“…Corneas with scarring and Salzmann's nodular degeneration have a normalthickness epithelium overlying a dense, hyper-reflective lesion overlying Bowman's layer on UHR-OCT [16]. Epithelial hypo-reflective cysts without basement membrane thickening are seen in Meesman's dystrophy [60]. Eyes with secondary corneal amyloidosis show deposits of amyloid above Bowman's layer, and destruction of Bowman's layer as the disease progresses [61].…”
Section: Ocular Surface Pathologymentioning
confidence: 99%
“…UHR-OCT can detect early secondary corneal amyloidosis as a dense spot in Bowman's layer [61]. Corneas with Thiel-Behnke Dystrophy have extensive deposits of hyper-reflective material in a saw-tooth pattern on the surface of Bowman's layer [60]. UHR-OCT images may become adjunct to clinical evaluation and provide an optical biopsy image in other conditions.…”
Section: Corneal and Ocular Surface Pathologymentioning
confidence: 99%
See 2 more Smart Citations